Molecular characterization and sequecing analysis of SARS-CoV-2 genome in Minas Gerais, Brazil. (October 2022) - Ferreira, Giulia Magalhães; Claro, Ingra Morales; Grosche, Victória Riquena; Cândido, Darlan; José, Diego Pandeló; Rocha, Esmenia Coelho; de Moura Coletti, Thaís; Manuli, Erika Regina; Gaburo, Nelson; Faria, Nuno Rodrigues; Sabino, Ester Cerdeira; de Jesus, Jaqueline Goes; et al.
Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), first identified in Wuhan, China, is the causative agent of the coronavirus disease 2019 (COVID-19). Since its first notification in São Paulo state (SP) on 26 th February 2020, more than 22, 300, 000 cases and 619, 000 deaths were reported in Brazil. In early pandemic, SARS-CoV-2 spread locally, however, over time, this virus was disseminated to other regions of the country. Herein, we performed genomic sequencing and phylogenetic analysis of SARS-CoV-2 using 20 clinical samples of COVID-19 confirmed cases from 9 cities of Minas Gerais state (MG), in order to evaluate the molecular properties of circulating viral strains in this locality from March to May 2020. Our analyses demonstrated the circulation of B.1 lineage isolates in the investigated locations and nucleotide substitutions were observed into the genomic regions related to important viral structures. Additionally, sequences generated in this study clustered with isolates from SP, suggesting a dissemination route between these two states. Alternatively, monophyletic groups of sequences from MG and other states or country were observed, indicating independent events of virus introduction. These results reinforce the need of genomic surveillance for understand the ongoing spread of emerging viral pathogens. Highlights: Analysis showed the circulation of B.1 isolates in the investigated location. Substitutions were seen into genomic regions related to important viral structures. Monophyletic cluster of isolates from SP and MG suggests a route of dissemination. Grouped MG and other regions isolates shows independent events of virus introduction.